The Effect of Workload, Motivation, and Time Management on Employee Performance in the Modern Retail Industry - Rifandi Arief; Justine Tanuwijaya; B. Medina Nilasari (Jurnal Penelitian, 2026)
This study aims to analyze the influence of workload, motivation, and time management on employee performance with job satisfaction as a mediating variable in the modern retail industry. This research employed a quantitative explanatory approach using survey data collected through the distribution of structured questionnaires with a five-point Likert scale to employees in modern retail companies. The data were analyzed using Structural Equation Modeling (SEM) to examine the direct and indirect relationships among variables. The results indicate that workload and time management have a positive and significant effect on job satisfaction, while motivation does not significantly affect job satisfaction. Furthermore, time management and job satisfaction have a positive and significant effect on employee performance, whereas workload and motivation do not have a direct effect on employee performance. Job satisfaction was found to fully mediate the relationship between workload and employee performance and partially mediate the relationship between time management and employee performance. The findings highlight the importance of workload management and improving employees’ time management skills in enhancing employee performance in the modern retail industry.